Opinion of Engineering Students on the Use of Live Online Lectures after the Pandemic - Chakraborty, Pinaki (Journal of Engineering Education Transformations, 2025)
The first outbreak of COVID-19 was reported in December 2019 and the disease took the shape of a pandemic in the next few months. Universities around the world imported lessons to their student mostly in online mode in 2020 and 2021. Thirty-five undergraduate computer science students were interviewed about their experience of attending online lectures during the COVID-19 pandemic. A quantitative analysis of their responses revealed that 43% of them felt that they can learn equally well from online and offline lectures, 49% felt that online lectures provide them flexibility which in turn helps them to perform better in academics and 54% felt that professors have improved their online teaching skills since the beginning of the pandemic. Further, a qualitative analysis revealed that students appreciate online lectures for allowing them to access ebooks and digital resources while attending lectures, and making it easier to study topics that require a lot of visualization and ask queries to professors. Consequently, 77% students said that a combination of online and offline lectures may be used in the future with students being allowed to choose how they learn. Alternatively, only online lectures may be scheduled on some days of the week so that students need not travel to the campus on those days.